Price Reversal : Overreaction and Liquidity in Sharia Manufacturing Shares Listed in the Indonesia Sharia Stock Index (ISSI) for the Period 2019 – 2021 - M. Rizkita Yoga; Siti Komariah (Institute of Computer Science (IOCS), 2022)
In choosing their desired types of investment, investors often considered several factors. The objective of this study is to examine the influence of overreaction and liquidity on price reversal phenomenon. The method used is descriptive research method with quantitative approach. We employed secondary data obtained from the 73 sharia manufacturing companies that are registered in the Indonesia Sharia Stock Index (ISSI) during the period 2019-2021, which is determined using several criteria. Based on the analysis results, it is indicated that there is an effect of overreaction and liquidity on price reversals on Sharia Manufacturing shares listed on the ISSI during the period 2019-2021. This study highlighted that overreaction phenomenon is a major problem for investors and the company itself.